Patterns of migration from Nepal to India through two border points. (2017) - Bohidar, Nabesh; Kaur, Navneet; Pandeya, Prakash; Awasthi, Sanjai
Estimating the number of Nepalis who migrate to India for work is difficult due to open borders and undocumented crossings. Consequently, identifying migrant flows and corridors, or 'who migrates to where' has very few answers. This paper presents data collected from a census of two border points on the Indo-Nepal border and analyses volume and patterns of Nepalis migrating to India. It provides an overview of origin and destination points and an analysis of seasonality of movement across the borders. A total of 41, 255 migrants were listed over the period of 12 months. Evidence generated from this border-point study reveals a much broader spectrum of migration than other studies conducted at only origin or destination areas. The findings reflect high volume of migration primarily from the Far-West Nepal to North, West and South India, and reveals migration to 15 states in India. The findings are expected to be useful to plan for development interventions, and to carry out further research on migration between Nepal and India.